MODERN CONCEPTUAL FRAMEWORK OF THE COSMIC SPACE CATEGORY - Klymenko , Lada; Yuzva , Solomiya (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the cosmic space category and its semantic meaning peculiarities. The interpretation of culture as a horizon of universal, that is, cosmic values, for all hours, was tied to the Cosmos. The national and cultural specificity of the cosmic space category was analyzed and its general characteristics were outlined. Also, the stages of the historical evolution of the studied category were profoundly focused. Given the results of the analysis the paper outlines the historical semantic shift and semantic expansion of this category. The vocabulary representing the concept was also structured. Medieval hymns that take their roots in folklore and folk epos turned out to be fruitful material for studying both linguocultural and worldview representations of the cosmic space category through the prism of the world’s perception of that particular time. Cosmological works of different time periods and modern scientific articles were used as reference corpus material for this particular research. The problems of reconceptualization and refiguration of the category of space were researched in the modern national worldview. Also, the difference between the nominative fields and their lexical realization of both concepts ESPACE and COSMOS were described, and the “historical layers’’ and their change of these two concepts were determined. The semantic field of the cosmic space category has significantly expanded and is characterized by the presence of multiple plans. It has a lot of different new meanings, including the reinterpretation of the cosmic space category in terms that can be attributed to the semantic fields of economic space, safety space, resource space. __________ References: • T. Kearney & Foreign Policy (Eds.). Globalization index (Washington DC: Carnegie, 2002). • Agnew, J. «Representing space: Space, scale and culture in social science.» Place / culture / representation,Duncan and D. Ley (Eds.) (London: Routledge, 1993): 251-271. • Cavallaro, Dani. Cyberpunk and Cyberculture: Science Fiction and the Work of William (2000). • Gibson (London: Athlone Press). • Foucault, Michel. «Des Espaces Autres.» Empan54, no. 2 (2004): 12, https://doi.org/ 10.3917/empa.054.0012. • Garretsen, Harry & Martin, Ron. «Rethinking (new) economic geography models: Taking geography and history more seriously.» Spatial Economic Analysis, 5 (2) (2010): 127-160. • Harvey, David. Spaces of global capitalism: Towards a theory of uneven geographical development (London: Verso, 2006). • Knoblauch, Hubert & Löw, Martina. «On the spatial refiguration of the social world.» Sociologica11(2), (2017): 1-27, https://www.rivisteweb.it/doi/10.2383/88197 [Accessed: July 30, 2021]. • Lestringant, Frank. Atelier Du Cosmographe Ou L’Image Du Monde a La Renaissance (L’) (Sciences - Sciences Humaines) (French Edition). 0 ed. Albin Michel, 1991. • Massey, Doreen. «Space-time, "science" and the relationship between physical and human geography.» Transactions of the Institute of British Geographers24(3) (1999): 261-276. • Munteanu, Ioana. Machina mundi. Architecture du cosmos dans la poésie sacrée du Moyen Âge latin. GE-NEC Yearbook. GE-NEC Yearbook 2002-2003 şi 2003-2004 (2006). • Suwala, Lech. “Concepts of Space, Refiguration of Spaces, and Comparative Research: Perspectives from Economic Geography and Regional Economics.” Forum Qualitative Sozialforschung / Forum: Qualitative Social Research 22, no. 3 (September 29, 2021), https://doi.org/10.17169/fqs-22.3.3789. • Administrateur, Super. “L’Univers serait une sphère.” Science Et Vie (December 29, 2020), https://www.science-et-vie.com/article-magazine/lunivers-serait-une-sphere. • CNRS Le Journal. “En route vers Uranus et Neptune ?,”d., https://lejournal.cnrs.fr/ articles/en-route-vers-uranus-et-neptune. • CNRS Le Journal. “On vient de découvrir les micronovae !,”d. https://lejournal.cnrs.fr/ articles/vient-de-decouvrir-les-micronovae • CNRS Le Journal. “Pernelle Bernardi, le sol martien dans l’objectif,”d. https://lejournal.cnrs.fr/articles/pernelle-bernardi-le-sol-martien-dans-lobjectif. • Français Facile – RFI. “Le français facile avec RFI : Apprendre le français avec l’actualité internationale,”d., https://francaisfacile.rfi.fr/fr/?from=savoirs. • Français Facile – RFI. “Le français facile avec RFI : Apprendre le français avec l’actualité internationale,”d. https://francaisfacile.rfi.fr/fr/?from=savoirs. • Français Facile – RFI. “Le français facile avec RFI : Apprendre le français avec l’actualité internationale,” n.d., https://francaisfacile.rfi.fr/fr/?from=savoirs. • La Vie mode d’emploi, leçon 2: Les Abysses, 30 mins, performance-conférence, 2018. Montrée au festival «Circonférence». • Leroy, Benoit. “Mission Artémis 1 : comment suivre le trajet vers la Lune de la fusée SLS ?” (TF1 INFO, September 3, 2022), https://www.tf1info.fr/sciences-et-innovation/video-nasa-objectif-lune-mission-artemis-1-comment-suivre-le-trajet-vers-la-lune-de-la-fusee-sls-2231184.html. • Le Monde en Sphères,d., http://expositions.bnf.fr/monde-en-spheres/index.html. • L’Allemagne Propose d’aider La Pologne à Surveiller Son Espace Aérien, d. https://www.aa.com.tr/fr/monde/lallemagne-propose-daider-la-pologne-%C3%A0-surveiller-son-espace-a%C3%A9rien/2740138. • Ouest-France.Fr, n.d. https://www.ouest-france.fr/sciences/espace/le-budget-de-l-agence-spatiale-europeenne-decolle-48c7dda2-6b47-11ed-a4bc-1fa2e638806c • Luminarium: From Les Echecs amoureux ("Amorous Chess") Manuscript made for Louise of Savoy, 15th c. Bibliothèque nationale de France, département des Manuscrits; Mss.fr.143, fo 20. • Трикомпонентна модель простору Середньовіччя, https://www.semanticscholar.org/ paper/Biblical-Cosmology%3A-The-Implications-for-Bible-Roberts/63e1b44d3474477155cf534b3ee4c4f331f3e5f6/figure/0 • Геліоцентрична система Коперника, https://phys.org/news/2016-01-heliocentric-universe.html